Reproductive status of male rat offspring following exposure to methamphetamine during intrauterine life: An experimental study - Zahra Khoshgoftar Some Saraii; Soroush Dianaty; Fatemeh Rouhollah; Nayereh Zare; Batool Ghorbani Yekta (Shahid Sadoughi University of Medical Sciences, 2023)
Abstract Background: Methamphetamine abuse during pregnancy is associated with maternal and fetal adverse outcomes. Methamphetamine induces reproductive damage in adults; however, its effect has not been studied during pregnancy. Objective: To investigate the effects of methamphetamine exposure during pregnancy on the reproductive system. Materials and Methods: 15 pregnant Wistar rats were divided into 3 groups (n = 5/group), they received daily intraperitoneal injections of saline or methamphetamine (5, and 10 mg/kg) from day 10 until the end of pregnancy. One adult male offspring was selected from each dam. Subjects were euthanized, and their testis was removed. Sperm samples from cauda epididymis were analyzed for sperm concentration, morphology, and motility. Terminal deoxynucleotidyl transferase dUTP nick-end labeling assay was used to detect apoptotic cells. Levels of B-cell lymphoma 2 protein (Bcl-2) and Bcl-2 associated X-protein were measured using Western blot. Results: Methamphetamine significantly decreased sperm concentration (5 mg vs. saline: p = 0.001, 10 mg vs. saline: p < 0.001), normal sperm morphology (saline vs. 10 mg: p = 0.001), and motility (p: saline vs. 5 mg = 0.004, 5 mg vs. 10 mg = 0.011, saline vs. 10 mg < 0.001) in a dose-dependent manner. There was a significantly higher number of terminal deoxynucleotidyl transferase dUTP nick-end labeling -positive cells and higher exposure. Moreover, Bcl-2 associated X-protein was increased, and Bcl-2 was decreased in these rats. Conclusion: The present study shows that chronic methamphetamine exposure during intrauterine period can induce apoptosis of seminiferous tubules and decrease sperm quality in adult rats. Moreover, we showed that the intrinsic apoptotic pathway is involved in this process. Further studies are required to identify the complete molecular pathway of these results.